Factors influencing the return of post-consumer products through reverse logistics: a conceptual model - Marcos, Jean; Fagundes, Alexandre Borges; Pereira, Delcio; Beuren, Fernanda Hänsch; Kobs, Fabio Fernando; Vaz, Caroline Rodrigues; Vieira, Cleide (CONTRIBUCIONES A LAS CIENCIAS SOCIALES, 2025)
THIS IS AN ARTICLE PUBLISHED BY CONTRIBUCIONES A LAS CIENCIAS SOCIALES (e-ISSN: 1988-7833) ON 2025-02-18, AVAILABLE ONLINE: https://doi.org/10.55905/revconv.18n.2-247 Abstract The growing consumption of goods has worsened environmental issues. To address this, Brazil implemented the National Solid Waste Policy, which includes tools like Reverse Logistics to return post-consumer products to their origin. Nonetheless, the actual return rate often falls short of expectations, as it is affected by multiple factors. This study aimed to identify variables influencing the return of post-consumer products through reverse logistics, focusing on aspects such as product lifespan, environmental responsibility, and consumer behavior. A comprehensive literature review led to the development and expert validation of a Conceptual Model. Statistical analysis of expert opinions revealed insights and potential trends, highlighting the possible interactions among the variables. Overall, this research contributes to understanding key influencing factors, advances scientific knowledge, and provides a conceptual basis for developing mathematical models in this emerging area of business logistics.
Keywords: Reverse logistics; Influence factors; Post-consumption goods; Consumer behavior; Conceptual model